The Effect of Mesoporous H-ZSM-5 Crystallinity as a CaO Support on the Transesterification of Used Cooking Oil - Amalia Putri Purnamasari; Meyga E. F. Sari; Desy T. Kusumaningtyas; Suprapto Suprapto; Abdul Hamid; Didik Prasetyoko (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
Transesterification of used cooking oil was carried out over calcium oxide supported on mesoporous H-ZSM-5 prepared from kaolin as solid base catalysts. Solid basic catalysts investigated in this study were characterized by XRD, FTIR spectroscopy, and N2 adsorption-desorption techniques. The XRD pattern showed peaks corresponding to the CaO and mesoporous ZSM-5 in the sample. The peak intensity of the CaO increased as CaO loading in ZSM-5 was increased. The characterization based on FTIR spectroscopy revealed that CaO/H-ZSM-5 solids have functional groups characteristics of both CaO and mesoporous H-ZSM-5 which appeared in the band at around 550 cm-1 and 480 cm-1. The isotherm of N2 adsorption-desorption of CaO/H-ZSM-5 indicated the type IV isotherm with the presence of hysteresis loop. For the catalytic activity, the biodiesel yield using catalyst of 10 % CaO/HZSM-5 (100 %), 30 % CaO/HZSM-5 (100 %), 50 % CaO/HZSM-5 (100 %) were 24.34, 27.37, and 29.73 %, respectively. It also related with the basic active site, when loading CaO increased, the basic active site also increased.